FAKTOR YANG MEMPENGARUHI MINAT BERKUNJUNG WISATAWAN KE TAMAN BUNGA CELOSIA BANDUNGAN KABUPATEN SEMARANG - Rizkiyanti, Dhania Febri (Pringgitan, 2023)
This research aims to see whether or not there is a relationship between location or place variables, prices or costs and services for visitors to the desire or interest in traveling in a tourist spot. Visitors who visit the tourist attractions of Celosia Flower Park became the population in this study. Purposive sampling method is an option in sampling. The sample taken in this research amounted to 100 informants who were visitors from tourist attractions. To analyze the data obtained using reliability testing, validity testing as well as multiple linear regression analysis. The result of this study is the presence of positive influences and significant locations to visit. Visitor services influence the interest of visits. Meanwhile, the cost of the attraction does not have a significant effect on the interest in visiting. Taken together, location, cost and visitor services have a positive and significant effect on visiting intentions with a very strong contribution. Cost has a higher influence on visiting interest.Keywords: Location, Cost, Visitor Services, Visit Interest